1986
DOI: 10.1111/j.1532-5415.1986.tb05763.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment

Abstract: All patients admitted to three medical services at the New York Hospital during a one-month period were screened with Folstein's Mini-Mental State Examination. The prevalence of cognitive impairment was 19.8% (23 of 116). Cognitively "impaired" patients, ie, those with a Folstein score less than 24, were older, sicker, and less physiologically stable than the cognitively "intact." The in-hospital mortality (17 versus 5%) and morbidity (39 versus 18%) rates were higher for the cognitively "impaired" patients; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Current evidence reveals higher rates of hospitalization7 and levels of co-morbidity among patients with dementia than among cognitively intact patients,812 with falls and behavioral problems being frequent causes of admission 13. AD and related disorders may be poorly recognized in community settings and if unrecognized may serve as a trigger for a host of undesirable adverse events upon hospitalization, including falls, unintended injuries, deconditioning, malnutrition, incontinence, nosocomial infections, over- or under-medication, and adverse responses to medications, leading to poorer outcomes 6,14–17.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence reveals higher rates of hospitalization7 and levels of co-morbidity among patients with dementia than among cognitively intact patients,812 with falls and behavioral problems being frequent causes of admission 13. AD and related disorders may be poorly recognized in community settings and if unrecognized may serve as a trigger for a host of undesirable adverse events upon hospitalization, including falls, unintended injuries, deconditioning, malnutrition, incontinence, nosocomial infections, over- or under-medication, and adverse responses to medications, leading to poorer outcomes 6,14–17.…”
Section: Introductionmentioning
confidence: 99%
“…While delirium has been widely recognized as an important complication of hospitalization for older persons, 4–6 more subtle reversible cognitive dysfunction related to acute illness has not been well examined. Fields et al 7 and Hickey et al 8 documented substantial rates of cognitive impairment during hospitalization of 19.8% and 31%, respectively; however, neither study analyzed the reversibility of the impairments or their relationship to delirium or dementia. In a separate study, Fields et al 9 examined a subgroup of the patients and found that 9 of 19 (47%) cognitively impaired medical patients improved their Mini‐Mental State Examination (MMSE) scores to their baseline level or by 4 or more points after 3 months.…”
mentioning
confidence: 99%
“…A total of 13 studies reported mortality as an outcome for cognitive impairment, six of which examined in-hospital mortality and six of which examined post-discharge mortality. 12,105,108,[138][139][140][141][142] One study 104 examined death rates per person per year in respect of in-hospital, post-discharge and cumulative mortality.…”
Section: Mortalitymentioning
confidence: 99%